The influence of marketing on consumption behavior at the bottom of the pyramid. Issue 2 (16th March 2015) - Jaiswal, Anand Kumar; Gupta, Shruti
Abstract : Purpose: – This paper aims to explore the nature and degree to which marketing affects consumption behavior of bottom of the pyramid (BOP) population. The objective of the study is to examine, identify and explain aspects of consumption behavior that evidences the influence of marketing practices on the BOP consumers. Design/methodology/approach: – The study uses a long interview-based approach for an in-depth qualitative investigation of consumption behaviors of BOP consumers. Findings: – Key findings that emerged from the research are: widespread usage of international brands and expenditure on products outside of the core bundle of consumption, susceptibility to sales promotions, need to look and feel good and use "fairness" creams, susceptibility to advertising and celebrity endorsements and influence of store personnel. Practical implications: – For managers, this research suggests a careful examination of the likely consequences of their marketing actions. A set of guidelines are provided to them for doing business in a responsible manner at the BOP markets. Social implications: – Recommendations for public policymakers are offered that stress on the need for ethical marketing exchanges to address the concern over possible exploitation of this vulnerable population. Originality/value: – Extant literature on BOP has largely been conceptual in nature, relying on various case studies. This study empirically examines the nature and influence of marketing in the purchase behavior of BOP consumers. This is perhaps the first study providing empirical support to the argument that the poor consumers divert their scarce financial resources from fulfilling basic needs to purchasing non-essential discretionary products under the influence of BOP marketing.